Flashlight : a novel [large type] - Choi, Susan, 1969- (Thorndike Press Large Print, 2025)
"One night, Louisa and her father take a walk on the beach. He's carrying a flashlight. He cannot swim. Later Louisa is found washed up by the tide, barely alive. Her father is gone. She is ten years old. In chapters that shift from one member to the next, turning back again and again to that night by the sea, Susan Choi's Flashlight chases the shockwaves of one family's catastrophe. Louisa is an only child of parents who have severed themselves from the past. Her father, Serk, an ethnic Korean born and raised in Japan, lost touch with his family when they bought into the promises of postwar Pyongyang and relocated to the DPRK. Her American mother, Anne, is estranged from her family after a reckless adventure in her youth. And then there is Tobias, Anne's illegitimate son, whose reappearance in their lives will have astonishing consequences. What really happened to Louisa's father? Why did he take Louisa and her mother to Japan just before he disappeared? And how can we love, or make sense of our lives, when there's so much we can't see?" --